Otoritas Tuan Guru Terhadap Dakwah Islam Pada Massyarakat Sasak Lombok: Analisis Teori Otoritas Max Weber - M Sulhan; Zulkipli Lessy (Indonesia, 2022)
This research study is about, ''The Authority of Tuan Guru in Islamic Da'wah to the Sasak Community of Lombok using Max Weber's theory of authority analysis, focused on Tuan Guru's authority as an educator, ulama and community leader on the island of Lombok, the theory of authority Max Weber is divided into three main classifications, namely traditional authority, charismatic authority and rational legal authority. This research was carried out based on the differences in the views of the community, characteristics, and the existence of ulama on the island of Java with scholars in the Sasak community of Lombok. Basically the acknowledgment of Tuan Guru (ulama) in the Lombok Sasak community, is based on several things, including: Culture, scholarship, social status and personality. The main purpose of this study is to see how the influence and form of Tuan Guru's authority in the Lombok Sasak community is, and how it affects the Islamic da'wah space on the island of Lombok. The analytical tool that the writer uses in this research is Max Weber's theory of authority, using descriptive-analytical method, data acquisition is based on literature review. The results of the research that the authors get are that Tuan Guru's authority is divided into three main authorities, namely traditional authority, charismatic authority, and rational legal authority and the influence of Tuan Guru's preaching on the Sasak people of Lombok has a high position in people's lives.